2022
DOI: 10.3390/antiox11061041
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic Stresses Elicitation Potentiates the Productiveness of Cardoon Calli as Bio-Factories for Specialized Metabolites Production

Abstract: Cultivated cardoon (Cynara cardunculus L. var altilis) is a Mediterranean traditional food crop. It is adapted to xerothermic conditions and also grows in marginal lands, producing a large biomass rich in phenolic bioactive metabolites and has therefore received attention for pharmaceutical, cosmetic and innovative materials applications. Cardoon cell cultures can be used for the biotechnological production of valuable molecules in accordance with the principles of cellular agriculture. In the current study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…Both coronatine and jasmonates initiate similar molecular pathways, such as anthocyanin accumulation, illustrating the versatility of these compounds beyond biotic stress responses. Abiotic stresses, also trigger secondary metabolites production pathways like anthocyanin biosynthesis ( Christie et al., 1994 ; Rudolf and Resurreccion, 2005 ; D’Alessandro et al., 2022 ).…”
Section: Improving Production Via Multistep Processesmentioning
confidence: 99%
“…Both coronatine and jasmonates initiate similar molecular pathways, such as anthocyanin accumulation, illustrating the versatility of these compounds beyond biotic stress responses. Abiotic stresses, also trigger secondary metabolites production pathways like anthocyanin biosynthesis ( Christie et al., 1994 ; Rudolf and Resurreccion, 2005 ; D’Alessandro et al., 2022 ).…”
Section: Improving Production Via Multistep Processesmentioning
confidence: 99%
“…These molecules are known for their great antioxidant, anti-inflammatory, antidiabetic, and anti-ageing activity [ 113 ]. The NaCl-induced salt stress application to a cultivated cardoon ( Cynara cardunculus L. var altilis ) callus increased the total phenolic and antioxidant content, which resulted in an increase in pro-collagen and aquaporin production in dermal cells, thereby boosting the production of bioactive compounds that can be used for cosmetic formulations [ 114 ]. Methyl jasmonate elicitation applied to Isatis indigotica hairy root cultures demonstrated outstanding results in the production of lignans.…”
Section: Main Biotechnological Approaches To Increasing the Productio...mentioning
confidence: 99%
“…The production of specific secondary metabolites can be boosted by treating the plant cell cultures with different type of stresses and growth factors (i.e. the ratio between auxins and cytokinines), or changing the growing conditions (light, temperature, oxygen) (Nielsen et al 2019;D'Alessandro et al 2022). For instance, it was shown that MS medium containing 0.2 mg/L IAA, 1.5 mg/L 6-BA, and 50 µM MeJA induced anthocyanins and PAs accumulation in apple callus due to MdMYB9 or MdMYB11 up-regulation (An et al 2015), as well as elicitation with 50 µM MeJA in Pyrus communis callus cultures up-regulated the expression of PcANR2a and PcLAR1, two genes important in the biosynthesis of PAs (Premathilake et al 2020), while light stress and nitrogen deficiency induced higher levels of PAs in poplar leaves (Gourlay and Constabel 2019).…”
Section: Introductionmentioning
confidence: 99%